Identification of Immune-Related Hub Genes in Thymoma: Defects in CD247 and Characteristics of Paraneoplastic Syndrome - Deng, Lin-Fang (Frontiers in Genetics, 2022)
Background Thymomas (Ts) and thymic carcinomas (TCs) are rare primary tumor of the mediastinum. Paraneoplastic syndrome (PNS) is an important feature of thymoma, which presents great challenges to clinicians. Methods The present study explores the Weighted Gene Co-Expression Network Analysis (WGCNA) to identity possible immunologic mechanism of Thymoma. RNA sequencing data from Thymoma samples are downloaded from the TCGA. Core genes are taken from the module that is closely related to the WHO stage of classification. Enhanced analysis using the online database “Metascape” and an overall survival (OS) analysis are carried out via the Kaplan-Meier method. The hub genes are obtained from the Protein-protein Interaction (PPI) network. In addition, we have jointly analyzed multiple sets of PNS data related to thymomas from other sources to verify the correlation between thymomas and PNS. The impact of hub genes on the prognosis of PNS is evaluated via ROC curve, with simultaneous analysis of immune infiltration by Cibersort. Findings 14 immune hub genes closely related to thymomas are found to jointly involve in the T-cell receptor signaling pathway. Comparing to normal thymus and type B1 / B2 thymoma, there is a less number of T cells in type A/B3 thymoma and thymic carcinoma. The expression of genes related to T cell receptor signaling pathway appears defective. The low expression of CD247 and the decrease in the number of mature T cells are common features among thymomas, specific pulmonary fibrosis, rheumatoid arthritis and systemic lupus erythematosus.